Reversals by the Supreme Administrative Court and Their Impact on Legal Certainty - Zaid Kamar Al-Sharifi , Assist. Lect. Badr (Basra studies journal, 2025)
This study examines the phenomenon of reversal in the rulings of the Supreme Administrative Court, which is considered one of the most significant judicial tools contributing to the development of judicial jurisprudence and the promotion of justice. The research analyzes the concept of administrative judicial reversal, identifies its justifications and characteristics that distinguish it from traditional judicial jurisprudence, and highlights its unique role as a mechanism for correction and development. The study concludes that reversal in the rulings of the Supreme Administrative Court is a double-edged sword. On one hand, it serves as an effective means for developing judicial jurisprudence and achieving justice; on the other hand, it may undermine legal certainty if not guided by clear standards and carefully designed mechanisms to reconcile conflicting judgments. Accordingly, the research recommends establishing explicit legal guidelines for practicing reversal, while reinforcing judicial independence as a fundamental condition for achieving the desired balance.